E-COMMERCE USER INTERACTION IN MULTI-ETHNIC SOCIETY IN PEMATANGSIANTAR CITY - Hasibuan, Adila Anatasya; Daud, Daud (Dinamika Bahasa dan Budaya, 2025)
This study examines the perceptions and experiences of multi-ethnic communities in Kelurahan Melayu, Pematangsiantar, towards the use of Shopee using a digital anthropology approach. Using qualitative methods through interviews and observations, it was found that the younger generation from various ethnicities have a positive view of Shopee, while the older age group, especially housewives, experience obstacles due to low digital literacy. Problems that arise include late delivery, product inconsistencies, and confusion about the payment system. The findings show that the meaning of Shopee features is constructed differently based on age, education, and ethnicity. The use of e-commerce has been proven to be a social practice that is full of cultural meaning, so an anthropological approach is needed to create inclusive digital services Keywords: Digital culture, Shopee, multiethnic society, anthropology, user perception.